FAKTOR – FAKTOR YANG MEMPENGARUHI CUSTOMER SATISFACTION PADA KONSUMEN ENERVON-C SELAMA COVID-19 DI JAKARTA - AFIFAH, WIDURI LULU; HARYANTI , DENNY SEPTA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
The aim of this research is to determine the influence of Attitude toward e-WOM, Customer Panic Buying Activity, and Brand Switching on Customer Satisfaction among Enervon-C users in Jakarta. In this study, secondary data and primary data were used, secondary data was obtained through journals while primary data was obtained through distributing questionnaires and obtaining 187 respondents from Enervon-C users in Jakarta. Using multiple linear regression analysis techniques. The results obtained are that Attitude toward e-WOM, Customer Panic Buying Activity, and Brand Switching influence Customer Satisfaction. Attitude toward e-WOM, Customer Panic Buying Activity, Brand Switching, Customer Satisfaction